(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The authors of given article elaborates on the history of formation of a new scientific direction - existential semiotics. This direction has been invented by a Finnish scientist, researcher of musical culture Eero Tarasti. The authors give description of the main provisions of existential semiotics as well as considers the origins of this concept. The central categories of the E. Tarasti’s work are such notions as "being", "doing" and "appearing". The scientist explains the most important social problems of the modern world by using these concepts. Methodological principles of E.Tarasti allow us to consider a variety of "small arts", for instance a theatrical performance. Different aspects of people’s daily life, which is connected with existential experiences, can become an object of existential semiotics.